![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx%2B2y%3D1%7D+%5Catop+%7B+x%5E%7B2%7D+-xy-2y%5E%7B2%7D%3D1+%7D%7D+%5Cright.+%3D%3E+%5Cleft+%5C%7B+%7B%7Bx%3D1-2y%7D+%5Catop+%7B%281-2y%29%5E%7B2%7D-%281-2y%29y-2y+%5E%7B2%7D%3D1++%7D%7D+%5Cright.+)
\left \{ {{x=1-2y} \atop {(1-2y)^{2}-(1-2y)y-2y ^{2}=1 }} \right. " alt=" \left \{ {{x+2y=1} \atop { x^{2} -xy-2y^{2}=1 }} \right. => \left \{ {{x=1-2y} \atop {(1-2y)^{2}-(1-2y)y-2y ^{2}=1 }} \right. " align="absmiddle" class="latex-formula">
1-4y+4y^{2}-1y+2y^{2}-2y^{2}-1=0
4y^{2}-3y=0
y(4y-3)=0
y₁=0 4y=3
y₂=
![\frac{3}{4} \frac{3}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B3%7D%7B4%7D+)
=0.75
x₁=1-2*0=-1 x₂=1-2*0.75=-0.5
Ответ (-1;0)Ü(-0.75;0.5)